Removal dye adsorption on to pineapple peel powder - Teong Hui Yin (School of Environmental Engineering University Malaysia Perlis, 2011)
The adsorption behavior of methylene blue on pineapple peel powder was studied on batch modes of operation. The operation parameters investigated including initial dye concentration (60-100mg/L0, contact time, pH of solution (2-12), adsorbent dose (1-5g/L). The adsorption was favorable at higher pH. The experimental data were analyzed using Langmuir and Freundlich isotherm model. Langmuir and Freundlich isotherm model constants and correlation coefficients were calculated. The langmuir isotherm model fits the data very well for the methylene blue on pineapple peel powder.